A Strategy for IMF Engagement on Social Spending. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
Interest in social spending issues has intensified over the last decade. This reflects concerns about rising inequality and the need to support vulnerable groups, especially in the aftermath of the global financial crisis. In line with this, the Fund has also increased its engagement on social spending issues. This paper outlines a strategy to guide IMF engagement on social spending issues going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet